2006
DOI: 10.1177/1359105306066637
|View full text |Cite
|
Sign up to set email alerts
|

Social Comparison Processes in Autobiographies of Adult Cancer Survivors

Abstract: Cancer survivors often compare their situations to other survivors' situations. However, types of social comparison processes used and resulting outcomes are not clearly delineated. This study explores usage and consequences of three social comparison styles (downward, upward and parallel) of adult cancer survivors in free narratives, using content analysis of 30 autobiographical books by survivors ranging in age from 30-70 (M = 54, SD = 10.04); 43 percent prostate cancer, 17 percent breast cancer and 40 perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
0
24
0
2
Order By: Relevance
“…Conversely, Chambers et al, 64 using the SF‐36, demonstrated an increase in QOL scores (domains of physical function, vitality, social function, emotional role, and mental health) for 30 individuals with short bowel syndrome after 6 months of home PN but no change in scores for the domains of bodily pain, general health, or physical component summary. Regardless of length of home PN dependency in the present study, participants perceived that life “could be a heck of a lot worse.” In addition, using downward social comparison (the process of comparing oneself to someone worse off), 65 , 66 participants saw their own situation as better than others who had a physical disability or cancer. These findings are comparable to home enteral nutrition consumers who also noted that home tube feeding was a small challenge when compared to other people's problems 67 …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Chambers et al, 64 using the SF‐36, demonstrated an increase in QOL scores (domains of physical function, vitality, social function, emotional role, and mental health) for 30 individuals with short bowel syndrome after 6 months of home PN but no change in scores for the domains of bodily pain, general health, or physical component summary. Regardless of length of home PN dependency in the present study, participants perceived that life “could be a heck of a lot worse.” In addition, using downward social comparison (the process of comparing oneself to someone worse off), 65 , 66 participants saw their own situation as better than others who had a physical disability or cancer. These findings are comparable to home enteral nutrition consumers who also noted that home tube feeding was a small challenge when compared to other people's problems 67 …”
Section: Discussionmentioning
confidence: 99%
“…Support programs can provide a place for social comparison, either upward (identifying with survivors who are doing well), downward (contrasting to other survivors who are doing worse), or parallel (Bellizzi, Blank, & Oakes, 2006). Upward social comparison has been linked to increased posttraumatic growth (Morris, Chambers, Campbell, Dwyer, & Dunn, 2011), indicating a mechanism by which peer-support may be linked to more positive assessment of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…According to Goethals (1986), this type of comparison is more likely to be made by people who feel threatened, or who have low self-esteem, to enhance their personal sense of well-being. Wills (1981) proposed that the same affect was achieved by making lateral comparisons to others seen to be at a similar level in coping with problems; this has also been referred to as parallel comparisons (Bellizzi, Blank, & Oakes, 2006). …”
mentioning
confidence: 99%